STRATEGI MEDIA SOSIAL CONTENT MARKETING HUMAS KEMENTERIAN KOPERASI DAN UKM DALAM REBRANDING KOPERASI MELALUI INSTAGRAM UNTUK MENGUBAH STIGMA MASYARAKAT TENTANG KOPERASI - Anggita Lestari Pangestuti Purnomo (2022)
The existence of a negative public stigma against Indonesian cooperatives which are considered undeveloped makes very few people interested in participating as members of cooperatives in Indonesia. Public Relations of the Ministry of Cooperatives and SMEs has a work program to rebrand cooperatives through social media Instagram @kemenkopukm. This study aims to find out how the social media content marketing strategy of the Ministry of Cooperatives and SMEs in rebranding cooperatives through lnstagram @kemenkopukrn to change the negative stigma of society about cooperatives. The research method used is qualitative with a case study approach and uses primary and secondary data sources. Data collection techniques were carried out by in-depth interviews and documentation. The data obtained were then analyzed through four stages, namely data collection, data reduction, data presentation and drawing conclusions. The results of this study indicate that the Public Relations of the Ministry of Cooperatives and SMEs is doing rebranding with a content marketing social media strategy, namely setting goals, mapping target markets, initiating and planning content, content creation, content distribution, collaboration with several related parties and content repetition and content marketing evaluation. but does not make content marketing improvements and content strengthening.